Decellularized bovine jugular vein and hand-sewn ePTFE valved conduit for right ventricular outflow tract reconstruction in children undergoing Ross procedure - Yuan, Haoyong; Lu, Ting; Wu, Zhongshi; Yang, Yifeng; Chen, Jinlan; Wu, Qin; Wu, Sijie; Zhang, Hong; Qian, Tao; Huang, Can (Frontiers in Cardiovascular Medicine, 2022)
Background: The Ross procedure is recommended as an optimal aortic valve replacement (AVR) in children and young adults due to several advantages. Nevertheless, multiple reconstructions of the right ventricular outflow tract (RVOT) with new valve conduits has caused some concern regarding the durability of the Ross AVR. Decellularization bovine jugular vein conduit (BJVC) (DP-BJVC) and hand-sewn expanded polytetrafluoroethylene valved conduits (ePTFE VC) are widely employed to reconstruct the RVOT with satisfactory long-term outcomes. However, few studies have compared the safety and efficacy between the two valve conduits. We aimed to evaluate the early outcomes and report our single center experience in the application of these conduits. Methods: Twenty-two pediatric patients (aged <18 years) who underwent Ross procedures with DP-BJVC and ePTFE VC in our center between 1 June, 2017 and 31 January, 2022 were enrolled. The Kaplan–Meier method was used to evaluate survival, freedom from RVOT reintervention, and freedom from RVOT graft dysfunction. Mixed-effects analysis with the Geisser–Greenhouse correction and Sidak’s multiple comparisons test for post-hoc analysis was employed to compare the peak gradient across the conduit at varying follow-ups. Results: All patients were followed up in full. The total early survival rate was 91.8%; two patients in the DP-BJVC group died. There was no significant difference in early mortality, cross-clamp time (p = 0.212), in-hospital stay (p = 0.469), and RVOT graft thrombosis or endocarditis between the two groups. There was similarly no significant difference between Kaplan–Meier freedom from RVOT graft dysfunction curve (P = 0.131). The transprosthetic gradient gradually increased over time in both groups, and was significantly higher in the DP-BJVC group at follow-up (P < 0.05). Conclusions: Both conduits show excellent early and midterm outcomes for RVOT reconstruction in the Ross procedure. We suggest that DP-BJVC is more suitable for infants, and ePTFE conduit is more suitable for older children who require larger conduits.